Development of Novel Gamified Online Electrocardiogram Learning Platform (GaMED ECG@TM) - May Honey Ohn; Khin Maung Ohn; Shahril Yusof; Urban D’Souza; Zamhar Iswandono Awang Ismail; Issa Mchucha (2020)
Following the advances of new technologies such as social networks, digital media, and the Internet, numerous learning materials nowadays incorporate multimedia technology to maximize the student learning experience. Greater student engagement, increased motivation and higher satisfaction of students using technology-enhanced learning can be achieved by gamification. Electrocardiogram (ECG) is a graphical image of cardiac electrical activity which needs to be interpreted timely and accurately in order to diagnose various types of life-threatening conditions in clinical practice. There is a call for innovative ECG instructional method that can actively engage learners and motivate them in order to interpret ECG correctly in a timely manner. In this case, we proposed and developed a gamified ECG learning platform in which ECG teaching materials were incorporated into gamification tool. A GaMED ECG@TM prototype was developed for ECG learning and then, GaMED ECG@TM software practicability was tested. An instructional design Analysis, design, development, implementation and Evaluation (ADDIE) model was followed in developing an online gamified learning platform GaMED ECG@TM. The GaMED ECG@TM platform incorporates a game-based technique as a strategy to deliver positive learning outcomes to students. In view of the need for technological innovations in medical education, this gamified learning platform provides the interactive self-paced activities structured as gamified lessons to enlighten the students with ECG knowledge.